GOVERNMENT RESPONSE: REVIEW OF RESEARCH IN CHINA AND PRACTICE IN INDONESIA - Judi, Tjatur Ermitajani (Magister Administrasi Publik Program Pascasarjana Universitas Ngurah Rai, 2021)
Studies in China and Indonesia have not explained how the actual practice of government response is based on factual observations. Based on the conceptual findings of research in China, this study elaborates on the practice of government response as a process in Indonesia. Research takes the object of research as the object of observation. Researchers review research achievements in China and intuitively observe practices in Indonesia. The results of the review and observation of government response research as a process show that almost all concepts, models and types of government responses in China are practiced by the Indonesian government. Studies in China and practice in Indonesia, following the perspective of governance, government-citizen interaction, response attitude, and the manner and content of government responses. Based on a study in China, which is very rich in concepts, the Indonesian government's response appears to be more chronological, careful, flexible, and considerate. Scholars in both countries can learn from and draw on experiences for further studies that are useful in the construction of respondent government models, as well as provide useful empirical examples for improving government response capacity.